Education and Providing Immunizations for Babies and Toddlers in the Pasir Putih Health Center Working Area, West Java: Edukasi dan Pemberian Imunisasi Bagi Bayi dan Balita di Wilayah Kerja Puskesmas Pasir Putih, Jawa Barat - Bunga Tiara Carolin; Shinta Novelia (KHD Production, 2023)
One of the efforts to reduce morbidity and mortality in children is by administering immunizations. Immunization is an effective and efficient strategy in improving national health status by preventing six deadly diseases, namely: tuberculosis, diphtheria, pertussis, measles, tetanus and polio. Counseling about the importance of immunization is an effort to increase knowledge about the importance of basic immunization for infants, so that it can reduce mothers' anxiety and fear about follow-up events after immunization which is the reason for mothers not to give immunizations. The method used is in the form of providing counseling materials on the importance of basic immunization for infants. This program will be implemented in March 2023 in toddlers in the Working Area of the Pasir Putih Public Health Center. The purpose of this community service is to provide education and provide immunizations for babies and toddlers. This activity is expected to increase knowledge and awareness of mothers about the importance of immunizing infants and toddlers.